2017
DOI: 10.1021/acs.iecr.7b01862
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Different Discrete Particle Methods Ability To Predict Gas-Particle Flow in a Small-Scale Fluidized Bed

Abstract: Several discrete particle methods exist in the open literature to simulate fluidized bed systems, such as discrete element method (DEM), time-driven hard sphere (TDHS), coarse-grained particle method (CGPM), coarse grained hard sphere (CGHS), and multiphase particle-in-cell (MP-PIC). The main difference between these methods is in the treatment of particle–particle interactions: by calculating collision forces (DEM and CGPM), using momentum conservation laws (TDHS and CGHS), or based on the particle stress mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…When one tracks the motion of only a representative particle or subset of particles through this latter approach, it is equivalent to the multiphase particle-in-cell (MP-PIC) approach, where the representative particles are commonly referred to as parcels (24,25). A hybrid option, where collision between the parcels is tracked to quantify direct parcel-parcel interaction (26)(27)(28), obviating the need to postulate a stress model, is also very popular. The PSD and dynamic evolution of particle properties are handled more efficiently by the particle-based methods.…”
Section: Modeling Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…When one tracks the motion of only a representative particle or subset of particles through this latter approach, it is equivalent to the multiphase particle-in-cell (MP-PIC) approach, where the representative particles are commonly referred to as parcels (24,25). A hybrid option, where collision between the parcels is tracked to quantify direct parcel-parcel interaction (26)(27)(28), obviating the need to postulate a stress model, is also very popular. The PSD and dynamic evolution of particle properties are handled more efficiently by the particle-based methods.…”
Section: Modeling Approachesmentioning
confidence: 99%
“…Bubble-like voids in dense fluidized beds and clusters in more dilute regions have indeed been captured by MP-PIC simulations (69). Recently, Lu et al (28) assessed the predictability of a coarse-grained EL approach with a hard-sphere contact model (27) by performing simulations of gas-particle flow in a small-scale fluidized bed and showed that the coarse-grained EL approach also captured bubbles and clusters.…”
Section: Emergence Of Structures At Different Scalesmentioning
confidence: 99%
“…More recently, CG-DEM was simulated in lab-scale bubbling beds with immersed tubes [66]. Simulations have been reported on the small-scale NETL bubbling bed challenge [88], including also the benefit of hard-sphere model for the collisions, which further considerably improves numerical efficiency.…”
Section: Bubbling/spouted/liquid Fluidized Bedsmentioning
confidence: 99%
“…This is also true for MP-PIC, but in comparison CFD-CGDEM relies on a significantly lower number of needed closures. Recent studies have also shown advantages regarding the performance of CFD-CGDEM in comparison to MP-PIC [45]. A rapidly increasing number of researchers use CFD-CGDEM.…”
Section: -1)mentioning
confidence: 99%